Response of Taro to Arsenic Contamination in the Ganga Basin of Eastern India - Kundu, Rajib; Pal, Sukanta; Bandopadhyay, Pintoo (JOURNAL OF ROOT CROPS, 2013)
Taro (Colocasia esculenta [L.] Schott.) is an important tropical tuber crop grown in Eastern and Northern States of India, where both cormels and leaves are eaten as a vegetable. During the past decade, arsenic (As) contamination in food chain has been reported from the Ganga basin of West Bengal and Bangladesh. The epidemiological studies show that chronic As poisoning can cause serious health problems to human beings through contamination of ground water and drinking water. Presence of As in vegetable and tuber crops was found to vary with crops and even among the cultivars of the same crop. Keeping this in view, field experiments were conducted at Nonaghata village of Nadia district during 2007-2008 and 2008-2009 to evaluate the varietal tolerance and accumulation of As in different taro cultivars. The experiment was laid out in Randomized Block Design with eight selected cultivars replicated thrice. The As accumulation was estimated using standard procedures. Results revealed that accumulation of As in different plant parts was in the order of leaf > petiole > cormel, irrespective of cultivars. Regarding varietal tolerance, cultivars, Telia, Muktakeshi and Nadia local accumulated lesser amounts of As in edible parts and produced greater cormel yield.